Perancangan WebAR sebagai media hybrid-education mengenai tujuan ke-13 dari SDGS - Prestiliano, Jasson; Jayanto, Lydia Rosita; Prasida, T. Arie Setiawan (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
The compulsive impact of human-caused climate change is now considered more of an environmental issue than a national security threat. The latest 2030 Agenda, the Sustainable Development Goals (SDGs), has a transformational vision to achieve universal literacy worldwide, including Indonesia. Addressing climate change is Goal 13 of 17 SDGs. This study uses a qualitative research method with a linear research strategy to develop hybrid-education media in the form of printed pamphlet media with Augmented Reality (AR) technology applications that run on the Web platform, namely WebAR. The procedure is triggered by the target image of the pamphlet, and the basic HTML structure uses the A-Frame 3D framework. This framework allows for 3D modeling and animation to be loaded into WebAR. This study shows that WebAR-based hybrid-education media can be used as an interactive means to study climate change issues and increase awareness and understanding of climate actions relevant to Goal 13 of the SDGs. The results also show that this media can increase public engagement in combating climate change issues.